Temperature effects on urea granules process to produce paddy fertilizer using top spray fluidized bed granulator - O, Rostam; Subramonian, Sivarao; SAID, MD RADZAI (Erpublication, 2014)
Temperature is often used in the convergence process chamber to control the level of humidity and the mass of granulated urea formation. However, the use of the expression of absolute temperature rarely investigated in urea granulation process but is limited in previous studies are often expressed as general reading. Therefore, this study was undertaken to determine an absolute temperature readings and its impact on urea granule. Features derived of urea granule diameter consist of 2 mm to 6 mm and hardness between 2.0 kg/grains to 4.0 kg/details. Experiments were conducted with the aid of experimental design, the One -Factor -At- A-Time (OFAT) as the initial method to determine the absolute temperature readings associated with the production of urea granule at optimum moisture and hardness. Granulation process was done experimentally using top spray fluidized bed granulator with fluidizing air profile and concentration of appropriate mechanisms commensurate with the size and hardness of the target. The information and data may be useful to study the optimization of the parameters as an inspection process and compare it with other variables to determine the optimal parameter used in the urea granulation process using Top Spray Fluidized Bedgranulator ( TSFBG ).